UPAYA PENINGKATAN ASUPAN MAKAN PADA PASIEN KANKER - S A Budi Hartati (PERSATUAN AHLI GIZI INDONESIA, 2007)
The adverse nutritional effects of cancer can be severe. Patient often fall in a condition of proteinenergy malnutrition which is called cachexia. Cachexia is symptom marked with anorexia,reducing of body weight, losing of muscle, organ dysfunction, hypo albuminemia, increasing ofbasal need, nutrition metabolism disorder and sigh of mal absorption. Cytokines that is producedafter cancer cell come into the body, is supposed cause anorexia. Researcher in the hospitalshow that significant weight loss and poor nutritional status were documented in more than 50percent of patients at the time of diagnosis. Surgery, radiation, chemotherapy, immuno nutrition,and transplantation are all types’ medical therapy that has been implemented to cure cancer.Medical therapy can generate side effect especially gastrointestinal disorder, which causereducing food intake. The objective of the diet management in patient with cancer is to fill needs ofnutrition through well-balanced diet. Nutrient requirement should contain energy 28-42 kcal/kgbody weight/day, protein 1.0-2.0 g/kg body weight/day, fat should be 20-30 percent from totalenergy need. Requirement of vitamin mount up to 10 times of requirement, whereas mineral suchas iron, cobalt, manganese, zinc chromium can mount 2-8 times of requirement. In conclusion dietmanagement is taking an important role to maintain the well-nutritional status.Keywords: cachexia. immuno nutrition